2003
DOI: 10.1037/0278-6133.22.6.638
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Perceived Stress and Health Behaviors in a Sample of Working Adults.

Abstract: The study examined associations between perceived stress and fat intake, exercise, alcohol consumption, and smoking behaviors. Data were from surveys of 12,110 individuals in 26 worksites participating in the SUCCESS project (D. J. Hennrikus, R. W. Jeffery, & H. A. Lando, 1995), a study of smoking cessation interventions. Linear regression analyses examined cross-sectional associations between stress level and health behaviors. Analyses were stratified by gender and controlled for demographics. High stress for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

34
395
6
10

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 547 publications
(459 citation statements)
references
References 39 publications
34
395
6
10
Order By: Relevance
“…Several studies have found no increase in drinking related to stressful life events (Droomers, Schrijvers, Stronks, Van De Mheen, & Mackenbach, 1999;Robertson, Xu, & Stripling, 2010;Welte & Mirand, 1995), social anxiety (Eggleson, Woolaway-Bickel, & Schmidt, 2004;Ham & Hope, 2006;Tran, Haaga, & Chambless, 1997) and posttraumatic stress disorder (Boscarino et al, 2006;Breslau, Davis, & Schultz, 2003;Najdowski & Ullman, 2009), and there are also studies reporting no drinking increase in people who have suffered pain (Yokoyama et al, 2009), sexual victimization (Testa, Livingston, & Hoffman, 2007) and effects of military combat (Fritch, Mishkind, Reger, & Gahm, 2010). Workrelated stress has a particularly uncertain relationship with drinking; sometimes distressed employees drink more (Ahola et al, 2006;Bobak et al, 2005;Richman, Shinsako, Rospenda, Flaherty, & Freels, 2002) and sometimes they do not (Hodgins, Williams, & Munro, 2009;Kouvonen et al, 2005;Ng & Jeffery, 2003). Other studies suggest that stress-induced drinking may be less common in certain age groups (such as older individuals who drink) (Graham & Schmidt, 1999;Pohorecky, 1991;Welte & Mirand, 1995) or in certain special roles (such as reduced drinking among socially anxious college students) (Ham, 2009;Ham & Hope, 2006).…”
Section: Ijadr International Journal Of Alcohol and Drug Researchmentioning
confidence: 99%
“…Several studies have found no increase in drinking related to stressful life events (Droomers, Schrijvers, Stronks, Van De Mheen, & Mackenbach, 1999;Robertson, Xu, & Stripling, 2010;Welte & Mirand, 1995), social anxiety (Eggleson, Woolaway-Bickel, & Schmidt, 2004;Ham & Hope, 2006;Tran, Haaga, & Chambless, 1997) and posttraumatic stress disorder (Boscarino et al, 2006;Breslau, Davis, & Schultz, 2003;Najdowski & Ullman, 2009), and there are also studies reporting no drinking increase in people who have suffered pain (Yokoyama et al, 2009), sexual victimization (Testa, Livingston, & Hoffman, 2007) and effects of military combat (Fritch, Mishkind, Reger, & Gahm, 2010). Workrelated stress has a particularly uncertain relationship with drinking; sometimes distressed employees drink more (Ahola et al, 2006;Bobak et al, 2005;Richman, Shinsako, Rospenda, Flaherty, & Freels, 2002) and sometimes they do not (Hodgins, Williams, & Munro, 2009;Kouvonen et al, 2005;Ng & Jeffery, 2003). Other studies suggest that stress-induced drinking may be less common in certain age groups (such as older individuals who drink) (Graham & Schmidt, 1999;Pohorecky, 1991;Welte & Mirand, 1995) or in certain special roles (such as reduced drinking among socially anxious college students) (Ham, 2009;Ham & Hope, 2006).…”
Section: Ijadr International Journal Of Alcohol and Drug Researchmentioning
confidence: 99%
“…Associations between OS and CVD risk may therefore be mediated through smoking. The presence of work-related stress (including high concentration demand and work dissatisfaction) predicted smoking status in middle-aged women (Jonsson, Johansson, Rosengren, Lappas, & Wilhelmsen, 2003), and OS has been associated with a broad range of smoking measures in both men and women (Ng & Jeffery, 2003). Associations between OS and levels of cigarette consumption particularly have emerged (Metcalfe, et al, 2003).…”
Section: Cigarette Smokingmentioning
confidence: 99%
“…Similarly, Chu and Kao (2005) found that people under high pressure were apt to be nervous and anxious (psychological aspect), prone to headaches, high blood pressure and heart attacks (physical aspect) and prone to absenteeism, high rates of quitting jobs, and low productivity (behavioral aspect). Many other research findings also found the existence, to varying degrees, of a relationship between stress and health (Dahlin, Joneborg, & Runeson, 2005;Ng & Jeffery, 2003). Pearlin (1999) and Lu (1997), reviewing previous studies, pointed out that certain variables play moderating roles in the relationship between stress and health.…”
Section: Introductionmentioning
confidence: 99%